2019
DOI: 10.3390/ma12091411
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonics for Biosensing

Abstract: Techniques based on plasmonic resonance can provide label-free, signal enhanced, and real-time sensing means for bioparticles and bioprocesses at the molecular level. With the development in nanofabrication and material science, plasmonics based on synthesized nanoparticles and manufactured nano-patterns in thin films have been prosperously explored. In this short review, resonance modes, materials, and hybrid functions by simultaneously using electrical conductivity for plasmonic biosensing techniques are exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 150 publications
0
33
0
Order By: Relevance
“…This indicated that a high concentration of DENV 2 E-proteins led to a lower noise of the signal, thus providing the maximum values of SNR. This effect was due to the stronger coupling of surface plasmon, which led to a stronger radiation damping of the surface [61,62]. In addition, the variation in SNR was almost similar to the binding kinetic analysis, as it is dependent on the resonance angle shift.…”
Section: Sensor Surface Characterizationmentioning
confidence: 51%
“…This indicated that a high concentration of DENV 2 E-proteins led to a lower noise of the signal, thus providing the maximum values of SNR. This effect was due to the stronger coupling of surface plasmon, which led to a stronger radiation damping of the surface [61,62]. In addition, the variation in SNR was almost similar to the binding kinetic analysis, as it is dependent on the resonance angle shift.…”
Section: Sensor Surface Characterizationmentioning
confidence: 51%
“…Using PTs to trap nanoscale particles, enhanced sensing is provided naturally by the nanoscale enhanced near fields [80]. Nanometric PTs based on nano-aperture designs also provide simplicity to be integrated on a chip that could contain sources, modulators and detectors.…”
Section: Discussionmentioning
confidence: 99%
“…Since their inception, plasmons have been implemented for a number of applications like light emitting diodes (LED) [ 54 , 55 ], biosensors [ 56 , 57 ], laser ablation [ 58 , 59 ] solar cells [ 60 , 61 , 62 , 63 ], nanolasers [ 64 , 65 , 66 ], Surface Enhanced Raman Spectroscopy (SERS) [ 67 , 68 ], waveguides [ 69 , 70 , 71 ] and lithography [ 72 , 73 ].…”
Section: Plasmonsmentioning
confidence: 99%